TEACHING STYLES AND APPROACHES: MEDICAL STUDENT’S PERCEPTIONS OF ANIMATION-BASED LECTURES AS A PEDAGOGICAL INNOVATION - Singh, Satendra; Singh, Savita; Gautam, Shikha (Pakistan Journal of Physiology, 2009)
Background: Despite over dependence on PowerPoint, few studies have focused on the value of animations versus static illustrations in Physiology teaching. This study was aimed to assess first year undergraduate medical student’s response towards the effectiveness of Animation-based Lectures (ABL) in Physiology and its comparison with other existing teaching modalities. Methods: A questionnaire with a five-point Likert scale rating ABL effectiveness on various aspects was administered and its comparison with other teaching methodologies was done. Results: Students had an overall positive attitude towards ABL and it was perceived as more useful than equivalent static learning material of PowerPoint or transparency which provided a passive unsuitable learning environment. Conclusion: This study suggests that educators should encourage use of ABL to sustain interest and try to achieve a balance between old form of board teaching and the new innovative world of animations without too reliance on PowerPoint to sustain interest and promote student engagement in lectures which may have a stimulatory effect on student learning methods